Ecodesign, sustentabilidade e o Projeto Limonada (ModaPalavra e-periódico, 2009)
This article relates the experience of “Projeto Limonada” , a line of clothing and accessories developed from the reuse of discarded jeans trousers. The Lemonade accompanies a new trend in fashion and contributes to the reduction of waste that pollute the environment. Based on the concepts and principles of sustainability, the Ecodesign, recycling and customization, the Limonada down its roots in the state of Santa Catarina and is moving toward building a world with more individuals informed, educated, aware, and training a more responsible society.
Keywords: Reuse; Ecodesign; Sustainability